The Effect of Video and Brochure Education on Mothers' Self-Efficacy in Preventing Childhood Diarrhea: A Quasi-Experimental Study - Merve Şahin Menteşe; Medine Yılmaz (Artuklu Health, 2026)
Introduction: This quasi-experimental study with a pretest-posttest control group design aimed to investigate the effects of different educational methods on mothers’ self-efficacy in preventing childhood diarrhea.Methods: Mothers of children under five years of age registered with a family health centre were selected using the simple random sampling method (n=120). The participants were then allocated by lottery to four groups (brochure=30, video=30, video + brochure=30 and control=30). The data collection tools were the Personal Information Form and the Maternal Self-Efficacy Scale for Preventing Early Childhood Diarrhea, Diarrhea Prevention brochure and video. The materials used for educational purposes were a brochure on how to prevent diarrhoea and a video on how to prevent diarrhoea. The data were collected first face-to-face and then by telephone over 2 months.Results: After the educational intervention, the proportion of mothers who knew what oral rehydration solution (ORS) was differed significantly among the groups (p